Movimento de paredes de domínio ferroelétricas com luz: descrição teórica e investigação do fenômeno em materiais policristalinos - Pimentel, Jonathan Ordoñez (Universidade Federal de São Carlos, 2019)
Ferroelectrics are material exhibiting a spontaneous polarization that may be switched by an electric external field. This behavior is provided to well-known ferroelectric domain walls motion. Recent research has proved the surprising ability to move ferroelectric domain wall under illumination with wavelength of 532 nm incident on a surface of single crystals of Barium Titanate (BaTiO3). In spite of experimental results concerning about this light-matter interaction, it is remarkable a lack of physical insight, as well as possibility to observe if occurrences of motion domain wall is due to single or poly crystal character. By using a phenomenological approaches based on Devonshire-Landau’s theory was possible make a development to describe a polarization-induced switching under light like perturbation of bound and free charge accumulated within domain wall. Accordingly, interactions between photons having lower energy that optical gap and screening charge give rise to fluctuation in depolarization electric field that serve as a driving force to polarization reorientation around the wall. This approach gives a satisfactory explanation to experimental facts observed in single crystals of BaTiO3, in addition, it allows to conjecture a correlation between the phenomenon occurrence with existence of charged domain wall as single crystal as polycrystal. It was prove that BaTiO3 coarse grain ceramics (grain size approx 50µm) contend 90-domains are possible a manifestation of polarization switching induced by light also, in this form, it was demonstrate the size grain dependence with evidence of this light-matter interaction, highlighted again the role-play of charged ferroelectric domain wall. In this way, here has made an extend to polycrystal materials that could lead to developed the next generation of photo-stimulated ferroelectric devices.
Keywords: BaTiO3; Domínios ferroelétricos; Paredes de domínio carregadas; Interação luz-matéria; Chaveamento da polarização com luz; Propriedades dielétricas; Ferroelectric domains; Ferroelectric charged domain walls; Light-matter interaction; Polarization switching induced by light; Electric properties; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA::MATERIAIS DIELETRICOS E PROPRIEDADES DIELETRICAS